Suara warga di lingkungan PLTU X dan kawasan pertambangan batubara: Studi Photovoice di Desa Z, Kabupaten Lahat, Sumatera Selatan - Najmah; Iwan Setiabudi; Marieska Verawaty; Wulandari Dwi Safitri; Tarisha Kahla Sabitha; Sasha Tiara Maharani; Ajeng Fathia Nurqanita; Fakhriyatiningrum; Jerri Agustan; Sahwan; Reza Yuliana; Nila Ertina; Swara Mega Hasanah; Mulawarman (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2026)
A Photovoice Analysis of Community Voices Around PLTU X on Mining Activities: A Basic AMDAL Training by Anak Padi Foundation, Lahat Regency. Coal-fired Steam Power Plants (PLTU) are one of the main sources of energy in Indonesia, but they are also significant contributors to environmental pollution and public health impacts. In Lahat Regency, coal mining areas as one of the fuels for PLTU are also spread around the PLTU, which adds to the impacts on health and the environment. This study aims to determine the voices or views of participants in the basic AMDAL (Environmental Impact Analysis) training who live around the PLTU area, especially residents of Z Village, regarding coal mining activities which are the main source of energy for the PLTU. The method used in this study is photovoice which involves participants to take photos that reflect their experiences and perspectives on environmental issues that are affected. The participants in this training have an age range of 18-75 years, totaling 27 people. There are 3 core stages of the photovoice process: making photos, collective interpretation and the dissemination process of the photo results (dissemination). The results show that most participants through photovoice expressed that the existence of mining activities and PLTUs has a negative impact on environmental quality, such as air pollution, lots of dust in residents' homes due to coal transportation activities, decreased farmer harvest production, and health problems to river pollution. This finding emphasizes the importance of involving residents in participatory environmental management and monitoring.This study recommends the need for more sustainable environmental evaluations, as well as strengthening community capacity in voicing the right to a healthy environment.